2017
DOI: 10.1160/th16-02-0123
|View full text |Cite
|
Sign up to set email alerts
|

Decreased platelet reactivity in patients with cancer is associated with high risk of venous thromboembolism and poor prognosis

Abstract: Platelets are suggested to play a crucial role in cancer progression and the prothrombotic state of cancer patients. Here, we aimed to examine the activation status of platelets in cancer patients and investigate their association with risk of death and occurrence of venous thromboembolism (VTE) in a prospective observational cohort study. We measured platelet surface P-selectin, activated glycoprotein (GP) IIb/IIIa and monocyte-platelet aggregate (MPA) formation in vivo and platelet response to ex vivo stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 38 publications
7
56
0
Order By: Relevance
“…While previous studies in non-cancer patients suggested that larger thrombocytes are functionally more active and elevated MPV was associated with various thrombotic events and a worse outcome [46,47], a higher MPV was associated with a significantly increased survival in patients with various solid tumors [29]. In this context, low MPV may reflect degranulated "exhausted" platelets that have already secreted their potentially tumor growth-promoting cytokines, and thus are associated with a worse outcome in cancer patients [48,49].…”
Section: Discussionmentioning
confidence: 94%
“…While previous studies in non-cancer patients suggested that larger thrombocytes are functionally more active and elevated MPV was associated with various thrombotic events and a worse outcome [46,47], a higher MPV was associated with a significantly increased survival in patients with various solid tumors [29]. In this context, low MPV may reflect degranulated "exhausted" platelets that have already secreted their potentially tumor growth-promoting cytokines, and thus are associated with a worse outcome in cancer patients [48,49].…”
Section: Discussionmentioning
confidence: 94%
“…32 Exhausted platelets were characterized by a high integrin activation and P-selectin expression in the absence of stimulating agents, and a reduced increase in the parameters after agonist stimulation. These changes might point to platelet activation in vivo , resulting in a secondary loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that platelets actively promote cancer progression through a variety of mechanisms, including protecting cancer cells from immune surveillance, negotiating the arrest of cancer cells in the microvasculature, and stimulating angiogenesis [15,21]. Decreased platelet surface expression of P-selectin and activated glycoprotein (GP)IIb/IIIa, in vivo and in response to protease-activated receptor (PAR)-1, PAR-4, and GP VI activation, has been associated with poor OS in patients with cancer [22].…”
Section: Discussionmentioning
confidence: 99%